2019
DOI: 10.1186/s41239-019-0146-1
|View full text |Cite
|
Sign up to set email alerts
|

Supporting self-regulated learning and personalization using ePortfolios: a semantic approach based on learning paths

Abstract: In the area of e-learning, there are new challenges to be overcome. One of them is to allow students self-regulation of their learning. Within this self-regulation process, students and teachers use technological tools to carry out their tasks. In general, these tools do not consider pedagogical aspects. Emerging approaches propose the use of electronic portfolios and semantic technologies to provide pedagogical characteristics that make tools more user-friendly for both teachers and students. This paper prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 22 publications
(21 reference statements)
0
16
0
4
Order By: Relevance
“…to confirm the extent to which their understanding is related to the material being studied, the lecturer gives the final assignment of the student explaining his understanding with the video format. ICT needs to help teachers to develop better pedagogical and teaching approaches, taking account of student differences (Romero et al, 2019). The management of the environment can thus contribute to the performance of a learner with e-learning courses as previous research suggests (Sharma et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…to confirm the extent to which their understanding is related to the material being studied, the lecturer gives the final assignment of the student explaining his understanding with the video format. ICT needs to help teachers to develop better pedagogical and teaching approaches, taking account of student differences (Romero et al, 2019). The management of the environment can thus contribute to the performance of a learner with e-learning courses as previous research suggests (Sharma et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The use of RSS in the e-portfolios such as in weblog has enabled the teacher educators to scaffold student teachers understanding through resolving ambiguities by giving immediate response (Chuang, 2008). Studies, such as Christen and Hoffman (2008), Harun and Jhee (2012), Denton and Wicks (2013), Sardegna and Dugartsyrenova (2014), Fahey and Cronen (2016), Gencel (2017), Cimermanova (2018), and Romero et al (2019), have shown that many student teachers are positive and gained benefits with the use of e-portfolios in the process of learning how to teach. This is due to the fact that student teachers are able to retrieve information posted via the e-portfolio in the form of PowerPoint presentations, notes, assignment tasks, points of group discussion, reflection notes, and peer assessment evaluation.…”
Section: Assisting Student Teachers In Learning How To Teachmentioning
confidence: 99%
“…Notably, Moshinskie (2001) states that it is essential to monitor the students' feelings or emotions because learners with a positive attitude have been seen as more confident and motivated to learn (Weston et al, 2019). Besides, considering the students as consumers of the educational systems and curricula is one of the main reasons to use digital learning strategies as a way to personalize learning experiences (Munro, 2018;Romero, Saucedo, Caliusco, & Gutiérrez, 2019).…”
Section: Sentiment Analysis For Educational Process Innovation and Damentioning
confidence: 99%